The Possibility of Measuring the Social Performance of Economic Enterprises and its Impact on Financial Reporting - A Case Study of the SAIDAL Group for the Period (2020-2023) - DJENNAI , Mohammed Alaeddin (Dirassat Journal Economic Issue, 2025)
This study aims to review a conceptual framework for measuring social performance. In addition to providing models of some contributions to social measurement, which has become one of the requirements of integrated financial reporting that combines financial and non-financial information. We conducted a field study in the SAIDAL Group, where we studied the reality of social responsibility in the Group and then tried to study it according to a number of proposed models. The study found that the measurement of social performance is difficult to critically assess due to a number of difficulties, most notably: the absence of binding legal legislation on the measurement of social responsibility, and the absence of standards and guidelines that clearly define social measurement methods.